1999
DOI: 10.1103/physrevb.59.5551
|View full text |Cite
|
Sign up to set email alerts
|

Silver-hydrogen interactions in crystalline silicon

Abstract: The creation of defects by hydrogen in silver-doped silicon crystals is investigated by deep-level transient spectroscopy. The electrical activity of the substitutional silver impurities can be totally removed due to defect formation with hydrogen atoms. However, this process includes the creation of intermediate electrically active silver-hydrogen complexes. One of the defects, Ag-H 1 , contains one hydrogen atom and introduces three levels in the energy gap. Another electrically active complex is formed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 26 publications
10
38
0
Order By: Relevance
“…On the other hand, this short-range potential may also be responsible for an electricfield dependence that has been reported for electron ͑hole͒ emission from double acceptor ͑donor͒ centers, in the case, for instance, of transition-metal impurities either isolated on substitutional lattice sites 26,27 or complexed with hydrogen. 28 In this case, however, the barrier lowering for emission is much smaller than in the case of the classical Poole-Frenkel effect. The observation of a weak dependence of the emission rate of the SnV1 level on the electric-field strength is thus indicative of this center being a double acceptor.…”
Section: A Deep-level Transient Spectroscopy "Dlts…mentioning
confidence: 93%
“…On the other hand, this short-range potential may also be responsible for an electricfield dependence that has been reported for electron ͑hole͒ emission from double acceptor ͑donor͒ centers, in the case, for instance, of transition-metal impurities either isolated on substitutional lattice sites 26,27 or complexed with hydrogen. 28 In this case, however, the barrier lowering for emission is much smaller than in the case of the classical Poole-Frenkel effect. The observation of a weak dependence of the emission rate of the SnV1 level on the electric-field strength is thus indicative of this center being a double acceptor.…”
Section: A Deep-level Transient Spectroscopy "Dlts…mentioning
confidence: 93%
“…Infact, several deep recombination centers in low-bandgap semiconductors manifested this behavior since the very beginning of the studies on limiting charge life-time centers (Wertheim, 1959). Particularly, in the last years an extensive thermal spectroscopy study revealed that this behavior is quite common for transition metals in semiconductors (Grillenberger, 2004;Knack et al, 2002;Sachse et al, 2000;Shiraishi et al, 1999;Yarykin et al, 1999). …”
Section: Dynamical Instability In Ionization-recombination Reactionsmentioning
confidence: 99%
“…This seemingly unlikely condition happens to be verified by several transition metal impurities in germanium, silicon, silicon carbide (Grillenberger, 2004;Knack et al, 2002;Sachse et al, 2000;Shiraishi et al, 1999;Wertheim, 1959;Yarykin et al, 1999), both in case of doubly and triply ionized centers. A treatment of photoconduction in semiconductor in which recombination is assured by multiply ionized centers can be found in ref.…”
Section: Bistability By Multiply Ionized Recombination Centersmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of hydrogen introduced is very low and is confined to the surface region. Much of the hydrogen is bound to P donors or B acceptors present in the material but annealing under a reverse bias (RBA) has the effect of driving the hydrogen deeper into the sample [164,165,166,167,168,169]. This method is particularly useful for a study of hydrogen related defects which dissociate around room temperature.…”
Section: Wet Etchingmentioning
confidence: 99%